Deskripsi Kegiatan Penangkapan Ikan Dengan Jaring Insang (gillnet) Di Kecamatan Air Rami Kabupaten Mukomuko, Provinsi Bengkulu - Zamdial Zamdial; Nurlina L. M. Nabiu; Mery Maryam (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2025)
Mukomuko Regency has a coastline of ± 98,218 km. There are several coastal zone districts as centers of capture fisheries, including Air Rami district. Nearly 70% of the population in Air Rami Sub-district are fishermen. One of the fishing gears used by fishermen in Air Rami District is a gill net. The purpose of this study is to describe the financial and technical aspects of gill net fishing by fishermen in Air Rami District, Mukomuko Regency, Bengkulu Province. The purpose of this study was to describe the financial and technical aspects of gillnet fishing by fishermen in Air Rami District, Mukomuko Regency, Bengkulu Province. The study was conducted from May to June 2025 using a survey method. Respondents were 10 gillnet fishing units. Data were collected using interviews. Data analysis was conducted using descriptive methods. The feasibility of gillnet fishing is assessed using four investment criteria : Net Benefit-Cost Ratio (Net B/C), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). Gillnet fishing units in Air Rami District typically use outboard motorboats (PMT) measuring 2.28 GT with a 15 HP engine, and gillnets with a mesh size of 2–2.5 inches. The average total investment of fishermen is Rp. 45,900,000, resulting in an annual income of Rp. 144,192,000 from 60 fishing trips. Financially, the gillnet fishing business is feasible based on a Net B/C value of 1.044 (>1), a positive NPV of Rp. 22,086,079, an IRR of 50%, and a PP of 4,867 years.